A novel pumping magnetorheological damper: Design, optimization, and evaluation. (October 2017) - Zhang, Xinjie; Li, Zhihua; Guo, Konghui; Zheng, Fumiao; Wang, Zhong
Magnetorheological damper has been widely used for improving vehicle ride comfort and handling because of its excellent performance. Numerous reinforced structures of magnetorheological dampers have been developed to enhance their dynamic performance and heat dissipation. This article presents a novel pumping magnetorheological damper with one-way pumping flow and dual-stage coil-in-cylinder magnetic system. Its dynamic model and inductive time constant are derived. Then, the structural parameters are optimized via a fast multi-objective genetic algorithm. Furthermore, a pumping magnetorheological damper prototype is tested and evaluated. The proposed pumping magnetorheological damper is able to perfectly balance the dynamic performance, heat dissipation efficiency, and structure flexibility via one-way pumping flow and coil-in-cylinder magnetic system, which has a promising application prospect in semi-active suspensions.